Star trek [compact disc, unabridged] : into darkness - Foster, Alan Dean, 1946- (Simon & Schuster Inc., 2013)
Kirk and Spock, graduates from Star Fleet Academy with contrasting personalities, must work together with their crew to defeat an alien captain intent on destroying all intelligent life in the galaxy.